The Case of Militarization of Civil Servants in the Palace Circle - Sultan Ridona Harahap (Politeknik Siber Cerdika Internasional, 2026)
Background: The era of President Prabowo Subianto’s administration has witnessed the resurgence of military involvement in civilian governance, challenging the principles of civil supremacy established after the 1998 reforms. The placement of active military officers in strategic civilian positions raises fundamental questions about constitutional boundaries and democratic governance in Indonesia. Objective: This study examines the legitimacy and constitutional implications of militarization in civilian government functions against the principles of civil supremacy and constitutional democracy as mandated by the 1945 Constitution of the Republic of Indonesia. Method: A normative juridical and political law approach is employed, utilizing statutory analysis, conceptual frameworks, and historical examination to assess the legal and political dimensions of military placement in civilian positions. Findings and Implications : The study reveals that militarization in the Prabowo era constitutes a form of state power reformulation that blurs the boundaries between civilian and military domains, threatening the independence of public accountability mechanisms and the principle of checks and balances. Military involvement in non-defense sectors such as food security, social welfare, and development projects represents an expansion beyond applicable legal norms, creating disharmony between political practices and constitutional design. Conclusion: This research contributes to the discourse on civil-military relations by demonstrating how contemporary militarization practices deviate from reform-era principles. It emphasizes the urgency of strengthening civilian control mechanisms and implementing regulatory reforms to ensure military professionalism while preserving democratic governance and constitutional order.